Benign acute viral myositis in African migrants: A clinical, serological, and pathological study. Issue 5 (30th August 2019) - Pancheri, Elia; Lanzafame, Massimiliano; Zamò, Alberto; Angheben, Andrea; Sartoris, Silvia; Zorzi, Antonella; Boaretti, Marzia; Signoretto, Caterina; Guglielmi, Valeria; Ferrari, Sergio; Tonin, Paola; Vattemi, Gaetano
Abstract: Background: Several viruses have been described as causes of acquired inflammatory myopathies; however, the mechanisms by which they cause muscle disease are still unclear. The aim of this study was to describe the laboratory features of benign acute myositis in a small case series. Methods: A detailed pathological and serological analysis was performed in five African migrants who developed an acute viral myositis complicated by rhabdomyolysis. Results: Muscle biopsies clearly documented an inflammatory myopathy with histological features similar to polymyositis including CD8+ T cells surrounding and invading nonnecrotic muscle fibers, CD68+ macrophages and major histocompatibility complex class I antigen upregulation. In addition, positivity for myositis‐specific antibodies (MSA), in particular anti‐aminoacyl tRNA synthetases, was found in the serum of two patients. Conclusions: Our study demonstrated that T‐cell mediated injury occurs in muscle of patients with acute viral myositis, and that MSA may be present in the serum of these patients.